2012
DOI: 10.1007/s00268-012-1514-3
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell Marker Bmi‐1 Expression is Associated with Basal‐like Phenotype and Poor Survival in Breast Cancer

Abstract: Bmi-1 status is an independent prognostic factor, which also is associated with tumor histological grade and basal-like phenotype. The high proportions of positive Bmi-1 expression in basal-like breast cancer may be related to the high aggressiveness behavior of this subtype of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 46 publications
(53 reference statements)
2
33
1
1
Order By: Relevance
“…In the present study, Bmi-1 protein is observed to exist in the cytoplasm of gastric lesions, opposite to its nuclear expression pattern in breast (Yin et al, 2011; Wang et al, 2012), pancreatic (Yin et al, 2011), cervical , esophageal squamous , tongue squamous (Häyry et al, 2010), colon , bladder (Qin et al, 2009) and endometric (Engelsen et al, 2008) cancer cells. Another group also found cytoplasmic Bmi-1 expression in oropharyngeal squamous cell carcinoma (Huber et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…In the present study, Bmi-1 protein is observed to exist in the cytoplasm of gastric lesions, opposite to its nuclear expression pattern in breast (Yin et al, 2011; Wang et al, 2012), pancreatic (Yin et al, 2011), cervical , esophageal squamous , tongue squamous (Häyry et al, 2010), colon , bladder (Qin et al, 2009) and endometric (Engelsen et al, 2008) cancer cells. Another group also found cytoplasmic Bmi-1 expression in oropharyngeal squamous cell carcinoma (Huber et al, 2011).…”
Section: Discussioncontrasting
confidence: 56%
“…Bmi-1(B-cell specific Moloney murine leukemia virus insertion site 1),a transcriptional repressor of polycomb group of transcription factors, had been found to involve in self renewal of hematopoietic [5], neuronal [6] and mammary [7] stem cells, and has been implicated in the tumorigenesis of various malignancies, including leukemia [8], lymphomas [9], non-small cell lung cancer [10], breast cancer [11] and nasopharyngeal carcinoma [12]. Moreover, Bmi-1 was also found to play a key role in tumor metastasis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Bmi-1 status is an independent prognostic factor, which also is associated with tumor histological grade and basal-like phenotype. The high proportions of positive Bmi-1 expression in BLBC may be related to the high aggressiveness behavior of this subtype of breast cancer (Wang et al, 2012). Apart from this study, Arnes et al have evaluated the relationship between Bmi-1 expression and basal-like phenotype.…”
Section: Discussionmentioning
confidence: 95%